Inertial sensors-determined match characteristics that serve as predictors of elite male badminton players’ performance levels - Abdullahi, Yahaya; Coetzee, Ben (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The study's purpose was to establish the inertial sensors-containing device (ISCD)-determined match characteristics that predict elite, male badminton players’ performance levels. Twenty-two (22) male single players (aged: 23.39 ± 3.92 years), who represented 10 African countries, participated in the study. Players were categorized as successful and less-successful players according to the results of five championships during two seasons. ISCD units (Catapult MinimaxV4), Polar Heart Rate Transmitter Belts, and digital video cameras were used to collect match data. ISCD-determined variables were corrected for match duration, and independent t-tests, cluster analysis, and a binary forward stepwise logistic regression were used for statistical analyses. A Receiver Operating Characteristic Curve (ROCC) indicated the validity of the group classification model. High-intensity accelerations per second were identified as the only ISCD-determined variable that showed a significant difference (p = 0.05) between groups. Furthermore, only high-intensity accelerations per second (p = 0.03) and low-intensity efforts per second (p = 0.04) were identified as significant predictors of group classification, with 76.88% of players that could be classified back into their original groups by making use of the ISCD-based logistic regression formula. The ROCC showed a value of 0.87. The identification of the last-mentioned ISCD-determined variables for the attainment of badminton performances emphasizes the importance of using badminton drills and conditioning techniques to improve not only the physical fitness levels of players but also their ability to accelerate at high intensities.